2021
DOI: 10.1111/1462-2920.15740
|View full text |Cite
|
Sign up to set email alerts
|

PrbP modulates biofilm formation in Liberibacter crescens

Abstract: Summary In Liberibacter asiaticus, PrbP is a transcriptional regulatory protein involved in survival and persistence during host infection. Tolfenamic acid was previously found to inhibit interactions between PrbP and the promotor region of rplK, resulting in reduced survival of L. asiaticus in the citrus host. In this study, we performed transcriptome analyses to elucidate the PrbP regulon in L. crescens, as it is phylogenetically the closest related species to L. asiaticus that can be grown in laboratory con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 75 publications
(179 reference statements)
4
7
0
Order By: Relevance
“…2 A, Table S7 ). The range of fold change obtained is in line with our previous reports involving chemical inactivation of transcriptional regulators in L. crescens [ 20 , 32 ]. As previously suggested, a contributing factor to these small changes in gene expression may be the high duplication time of L. crescens, which further leads to low transcriptional activity.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…2 A, Table S7 ). The range of fold change obtained is in line with our previous reports involving chemical inactivation of transcriptional regulators in L. crescens [ 20 , 32 ]. As previously suggested, a contributing factor to these small changes in gene expression may be the high duplication time of L. crescens, which further leads to low transcriptional activity.…”
Section: Resultssupporting
confidence: 91%
“…asiaticus [ 51 ], and their involvement was proposed in the initial attachment and colonization of the bacterium within the host. In agreement with these observations, we recently reported that in L. crescens , the global regulator PrbP binds to the promoter region of visN and up-regulates its expression under biofilm forming conditions [ 32 ]. PrbP was also found to induce the expression of mucR , consequently repressing the expression of rem , an activator of motility genes [ 32 ].…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations